Kajian Produk Kreatif sebagai Salah Satu Komponen Pembentuk Citra Pariwisata Jakarta dalam Meningkatkan Daya Saing Studi Kasus: Souvenir Ondel-Ondel - Erna Ervina Wati; Yustisia Pasfatima Mbulu; Fahrurozy Darmawan (Journal of Tourism Destination and Attraction, 2015)
This study aims to analyze how the competitiveness of creative products, especially souvenirs ondel-ondel so as to represent the image of tourism in Jakarta. The research design used in this study is a qualitative research design, using secondary data and primary data. Data collection methods used are passive participant observation and interviews as well as incidental sampling and purposive sampling into the techniques used in the determination of informant. The analysis of this study was to examine the ondel-ondel souvenir with competitiveness indicators, authenticity, and are classified into tourism image-forming component. The results showed that as the creative product, ondel-ondel souvenir has a competitive advantage in the aspect of authenticity, but in other aspects are still weak. From the other side, most respondents agree that ondel-ondel souvenir can represent the image of Jakarta destinations.